Greener ullmann-type coupling of aryl halides for preparing biaryls using reusable Pd/ZrO2 catalyst - Dumbre, Deepa K.; Wakharkar, Radhika D.; Choudhary, Vasant R. (Synthetic Communications, 2011)
Biaryls with excellent yields can be prepared by the Ullmann-type coupling of aryl halides in the presence of potassium carbonate (as a base) and dimethylformamide (as a solvent), at 140 degrees C, using a reusable Pd (2.5wt%)/ZrO2 catalyst. The product yield of 4-iodoanisole coupling is strongly influenced by the catalyst preparation method, solvent, and base.
Keywords: Aryl halides; Biaryls; Pd; Ullmann coupling reaction; ZrO2

Clay encapsulated Cu(OH)(x) promoted homocoupling of arylboronic acids: an efficient and eco-friendly protocol - Dar, Bashir Ahmad; Singh, Snehil; Pandey, Nalini; Singh, A. P.; Sharma, Priti; Lazar, Anish; Sharma, Meena; Vishwakarma, Ram A.; Singh, Baldev (Applied Catalysis A-General, 2014)
Cu(OH)(x) has been encapsulated over montmorillonite-KSF by simple ologomeric deposition strategy. The resulting catalyst has been employed for selective homocoupling of arylboronic acids under ambient conditions without requirement of any ligand or base. This catalyst is easy to recover and shows excellent reusability without losing its activity. Techniques like XRD, SEM, TPR, IR, BET surface area measurement and XPS were used to characterize the catalyst. The present method promises for the simple and clean homocoupling of arylboronic acids. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Biaryls; clay; Copper; Heterogenous catalyst; Homocoupling

Modular synthesis of biaryl-substituted phosphine ligands: application in microwave-assisted palladium-catalyzed C-N cross-coupling reactions - Singh, Chandani; Rathod, Jayant; Jha, Vishwajeet; Panossian, Armen; Kumar, Pradeep; Leroux, Frederic R. (European Journal of Organic Chemistry, 2015)
Biaryl-substituted monophosphine-based ligands have been synthesized by transition-metal-free ARYNE cross-coupling reaction of aryllithiums with 1,2-dibromobenzene and subsequent regioselective functionalization through bromine-lithium interconversion. These ligands were employed in palladium-catalyzed C-N bond-forming reactions. The reaction was found to be general with wide substrate applicability. A wide variety of both primary and secondary amines were successfully coupled with an array of differently substituted halobenzenes under microwave irradiation to give the expected products in good to excellent yields. A number of biaryl-substituted phosphine ligands screened for the coupling reaction showed that steric bulk and the electronic properties of substituents on phosphorus play a crucial role in governing the catalytic activity of C-N cross-coupling reactions.
Keywords: Biaryls; Cross-coupling; Homogeneous catalysis; Microwave chemistry; Palladium; Phosphines; synthetic methods

Advances in C(sp(2))-H/C(sp(2))-H oxidative coupling of (Hetero)arenes using 3d transition metal catalysts - Bansal, Sadhna; Shabade, Anand B.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2021)
C-H/C-H oxidative coupling has emerged as a straightforward and powerful technique for the construction of (hetero)biaryls, with substantial application to drug discovery, agrochemicals, biology, and material sciences. Mainly aryl-aryl, aryl-heteroaryl, and heteroaryl-heteroaryl couplings via double C(sp(2))-H activation using 4d or 5d noble transition metal catalysts have been extensively studied. Considering the earth-abundant and inexpensive nature of 3d transition metals, the sustainable development of C(sp(2))-H/C(sp(2))-H oxidative coupling employing such metal catalysts has gained significant attention. In this review, we present a comprehensive overview of C(sp(2))-H/C(sp(2))-H oxidative coupling of (hetero)arenes catalyzed by 3d transition metals.
Keywords: (hetero)biaryls; 3d transition metal; Biaryls; C-H activation; cross-dehydrogenative coupling